Creating an English Computer Game as an Interactive Material in Teaching English to Young Learner (TEYL) - Aprilian Ria Adisti (Register Journal, 2016)
This study aims at explaining the interactive materials that were needed in Teaching English to Young Learner, creating an English computer game into an interactive material, and examining the effective of the implementation of an English computer game as an interactive material in Teaching English to Young Learner to the first-grade students of elementary school. The study used Research and Development (R&D) adapted from Hutchinson and Water (1987:53-56) and by Borg and Gall (1985). The study had seven stages, they were: (1) conducting a need analysis of the first-grade students, (2) writing the course grid such as lesson plan and map of interactive material, (3) developing preliminary form of English computer game, (4) preliminary field testing by English teacher, English learning expert, and ICT learning expert, (5) revising the English computer game, (6) trying out, and (7) writing the final draft of the use of English computer game for Teaching English to Young Learners. The result of the study showed that students got better achievement in learning English. It could be seen from the result between pre-test and post-test using t-test formula. The result showed t value > t table; 7.165 > 2.021, it meant that there was a significant difference between pre-test and post-test. The post-test was higher that pre-test. The mean of pre-test was 65.2 while the mean of post-test was 87.44. It was also strengthened by the result of the interview which concluded that students liked learning English through this interactive material.